An Aqueous Extract of Herbal Medicine ALWPs Enhances Cognitive Performance and Inhibits LPS-Induced Neuroinflammation via FAK/NF-κB Signaling Pathways - Lee, Ju-Young; Joo, Bitna; Nam, Jin Han; Nam, Hye Yeon; Lee, Wonil; Nam, Youngpyo; Seo, Yongtaek; Kang, Hye-Jin; Cho, Hyun-Ji; Jang, Young Pyo; Kim, Jeongyeon; We, Young-Man; et al. (Frontiers in Aging Neuroscience, 2018)
Recent studies have shown that Liuwei Dihuang pills (LWPs) can positively affect learning, memory and neurogenesis. However, the underlying molecular mechanisms are not understood. In the present study, we developed ALWPs, a mixture of Antler and LWPs, and investigated whether ALWPs can affect neuroinflammatory responses. We found that ALWPs (500ug/ml) inhibited lipopolysaccharide (LPS)-induced proinflammatory cytokine IL-1β mRNA levels in BV2 microglial cells but not primary astrocytes. ALWPs significantly reduced LPS-induced cell-surface levels of TLR4 to alter neuroinflammation. An examination of the molecular mechanisms by which ALWPs regulate the LPS-induced proinflammatory response revealed that ALWPs significantly downregulated LPS-induced levels of FAK phosphorylation, suggesting that ALWPs modulate FAK signaling to alter LPS-induced IL-1β levels. In addition, treatment with ALWPs followed by LPS resulted in decreased levels of the transcription factor NF-kB in the nucleus compared with LPS alone. Moreover, ALWPs significantly suppressed LPS-induced BV2 microglial cell migration. To examine whether ALWPs modulate learning and memory in vivo, wild-type C57BL/6J mice were orally administered ALWPs (200 mg/kg) or PBS daily for 3 days, intraperitoneally injected (i.p.) with LPS (250 ug/kg) or PBS, and assessed in Y maze and NOR tests. We observed that oral administration of ALWPs to LPS-injected wild-type C57BL/6J mice significantly rescued short- and long-term memory. More importantly, oral administration of ALWPs to LPS-injected wild-type C57BL/6J mice significantly reduced microglial activation in the hippocampus and cortex. Taken together, our results suggest that ALWPs can suppress neuroinflammation-associated cognitive deficits and that ALWPs have potential as a drug for neuroinflammation/neurodegeneration-related diseases, including Alzheimer’s disease (AD).